2014
DOI: 10.1590/0004-2730000003538
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of the metabolic syndrome increases through the quartiles of thyroid stimulating hormone in a population-based sample of euthyroid subjects

Abstract: Objective: The aim of the study was to assess the prevalence and characteristics of metabolic syndrome (MetS) and its elements in relation to TSH in euthyroid subjects. Materials and metho ds: In the cross-sectional study, 2,153 euthyroid adults, 47.2 ± 14.5 years (20-94) with no current antithyroid or thyroid replacement therapy were enrolled. All participants filled a questionnaire on past and current morbidities, medication and smoking. Body weight, height, waist circumference, serum TSH, glucose and lipids… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 28 publications
1
21
4
Order By: Relevance
“…The significant positive correlations between CRP and IL-6 in both OB groups as well as in the hypothyroid patients with a normal BMI (Group C) corresponded to data of other authors reporting that thyroid deficiency and visceral obesity are independently associated with increased CRP and IL-6 as markers of low-grade chronic inflammation of adipose tissue [9][10][11]. Some found that euthyroid subjects with TSH in upper normal range (2.5-4.5 mU/l) and normal FT3 and FT4 had increased BMI and significantly higher prevalence of metabolic syndrome [12,13]. In this respect, thyroid hormone deficiency seems to be a possible pathogenetic factor, which aggravates the metabolic disturbances.…”
Section: Discussionsupporting
confidence: 83%
“…The significant positive correlations between CRP and IL-6 in both OB groups as well as in the hypothyroid patients with a normal BMI (Group C) corresponded to data of other authors reporting that thyroid deficiency and visceral obesity are independently associated with increased CRP and IL-6 as markers of low-grade chronic inflammation of adipose tissue [9][10][11]. Some found that euthyroid subjects with TSH in upper normal range (2.5-4.5 mU/l) and normal FT3 and FT4 had increased BMI and significantly higher prevalence of metabolic syndrome [12,13]. In this respect, thyroid hormone deficiency seems to be a possible pathogenetic factor, which aggravates the metabolic disturbances.…”
Section: Discussionsupporting
confidence: 83%
“…Several cross‐sectional studies have explored the association between THs or TSH and MetS in euthyroid subjects. Most of these studies only reported the association between TSH within reference range and the prevalence of MetS, which showed that serum TSH levels were positively associated with MetS in different populations . Another three cross‐sectional studies demonstrated that higher FT3 and lower FT4 levels were associated with higher odds ratio of MetS .…”
Section: Discussionmentioning
confidence: 99%
“…To date, only several cross‐sectional studies have evaluated the association between THs or TSH and MetS in euthyroid subjects, and a few studies assessed just MetS components individually rather than the syndrome as a whole . Additionally, only one cohort study evaluated the association between TSH levels and the prevalence and incidence of the MetS in older people (aged 70‐79 years) .…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, it may often be recognized as one of the metabolic syndrome features. Also, TSH levels have been associated with increased body fat and BMI, as well as increased cardiovascular risk [35], although the studies are still controversial [36,37]. Within the reference range, it was already acknowledged that TSH levels seem to increase the BMI proportionally [38].…”
Section: Discussionmentioning
confidence: 99%